A dual inhibitory mechanism restricts msl-2 mRNA translation for dosage compensation in Drosophila. - Beckmann, K.; Grskovic, M.; Gebauer, F.; Hentze, M.W. (Cell, 2005)
Drosophila MSL-2 is the limiting component of the dosage compensation complex. Female flies must inhibit msl-2 mRNA translation for survival, and this inhibition is mediated by Sex-lethal (SXL) binding to sites in both the 5' and the 3' untranslated regions (UTRs). Here, we uncover the mechanism by which SXL achieves tight control of translation initiation. SXL binding to the 3'UTR regulatory region inhibits the recruitment of 43S ribosomal preinitiation complexes to the mRNA. Ribosomal complexes escaping this block and binding to the 5' end of the mRNA are challenged by SXL bound to the 5'UTR, which interferes with scanning to the downstream initiation codon of the mRNA. This failsafe mechanism thus forms the molecular basis of a critical step in dosage compensation. The results also elucidate a two step principle of translational control via multiple regulatory sites within an mRNA.